(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Fetuin-A, a plasma glycoprotein, is a strong calcification inhibitor whose polymorphism in kidney stone disease has received the least attention. The aim of the study was to compare fetuin-A gene polymorphisms and their expression in renal stone disease. Methods: A total of 100 participants, including 50 cases and 50 control subjects were enrolled in the study. Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR–RFLP) was used to analyse the fetuin-A c.742C>T and c.766C>G Single Nucleotide Polymorphisms (SNPs). Biochemical parameters were assayed. SPSS 23 was used for statistical analysis. Results: The distribution of Fetuin-A c.742C>T and Fetuin-A c.766C>G mutant and wild alleles did not differ significantly. The polymorphisms in the fetuin A gene were not significantly correlated with their expression. Serum fetuin A was insignificantly lowered(p=0.43), uric acid and creatinine were significantly higher (p=0.012 and p=0.046 respectively) in cases.eGFR was reduced significantly (p<0.0001) in cases suggesting a renoprotective role of fetuin A. Significant positive correlation was observed between fetuin A and calcium levels. Conclusion: According to the study, there is no conclusive link between renal stone disease and fetuin A gene variations. Lowered Fetuin A levels in patients with renal stone disease suggest a protective role of fetuin A. Small sample size is the limitation of the study. However, it may be considered as a pilot study and further investigations may be carried out to further explore the role of fetuin A in kidney stone disease.